Jail Inmates in 2020 - statistical tables - Minton, Todd D. (Prison and Jail Inmates at Midyear, Jail Inmates, 2021)
This report is the 34th in a series that began in 1982. It describes the number of inmates held in local jails, jail incarceration rates, inmate demographics, conviction status and most serious offense, the number of admissions to jail, jail capacity, inmate turnover rates, and staff employed in local jails.